(untitled) - Crawford, Joel; (Film director); Reynolds, Ryan; Cage, Nicolas; 1965-; Stone, Emma; 1988-; Keener, Catherine; (Screenwriter); Hageman, Dan; Swift, Mark; Logan, Bob; et al. (Universal Pictures Home Entertainment, 2021)
The Croods need a new place to live. So, the first prehistoric family sets off into the world in search of a safer place to call home. When they discover an idyllic walled-in paradise that meets all their needs, they think their problems are solved, except for one thing. Another family already lives there: the Bettermans.
Keywords: Prehistoric peoples; Juvenile films; Families; Juvenile films; Computer animation films; Animated films; Action and adventure films